GENDER SPECIFICS OF SUBFRACTIONAL PLASMA LIPOPROTEIDS DISTRIBUTION - I. N. Ozerova; V. A. Metelskaya; N. E. Gavrilova (Кардиоваскулярная терапия и профилактика, 2016)
Aim. To find out, whether there is specifics of subfractional distribution of plasma  lipoproteides  in men  and  women depending  on coronary atherosclerosis.Material and methods. Totally 310 patients included (203 males, 107 females), underwent coronary arteriography; lesion of artery was assessed with Gensini Score  (GS). Subfractional spectrum  of plasma lipoproteides  was studied via electrophoresis in 3% polyacrylamid gel with Lipoprint system (Quantimetrix Lipoprint System, USA).Results. In the  group  without lesion (GS =0) gender  differences  of lipids, apolipoproteides and glucose utilization parameters were absent. Among coronary  atherosclerosis patients  (GS >0)  males  had  lower concentrations of low and high density cholesterol (LDL, HDL), as Apo A1 and Apo B. Males with GS =0, as with GS >0 differed from females by lower lipoproteides of intermediate density (LID) — LID B and LID A, and higher part of LDL 2 and small dense  particles LDL 3, but mean size of LDL particles was smaller. There were no differences in HDL subfractions distribution  among  men  and  women,  but  in men  only if  coronary atherosclerosis, there were lower cholesterol concentrations found in all HDL subfractions.Conclusion. Gender differences are revealed in subfractional spectrum of LID and LDL: in men regardless coronary atherosclerosis with the same and even lower level of LDL cholesterol there was accumulation of more atherogenic  small dense  LDL particles. Gender differences in the part of HDL subfractions were not found, but in men concentration of cholesterol in each of subfractions, with coronary lesion, was lower than in women.